Implementation Of Good School Governance In Improving School Wellbeing In Primary Education - Kumalasari, Lina; Martono, S.; Pramono, Suwito Eko; Sugi, Sugi (Proceedings of International Conference on Science, Education, and Technology, 2024)
This study aims to identify and analyze the application of the principles of good school governance in the context of the Merdeka Curriculum and evaluate its impact on school wellbeing. A qualitative approach with a case study design was used to explore in depth the practices of good school governance in several schools that have implemented the Merdeka Curriculum. Data were collected through in-depth interviews, focus group discussions (FGDs), observation, and document analysis. The results show that the principles of transparency, accountability, participation, and fairness are applied in various innovative ways. Transparency is realized through open communication between the school and stakeholders. Accountability is implemented through periodic reporting and performance evaluation. Participation involves students, teachers and parents in decision-making while equity ensures equal access to resources and learning opportunities. The impact of implementing these principles is very positive on school well-being, which includes improving students' physical, emotional, social and academic well-being. This study concludes that the implementation of good school governance significantly contributes to improving school well-being and supports students' holistic development in the context of Merdeka Curriculum.